Nagość jako strategia promocyjna kina polskiego lat 80. - Zwierzchowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article examines how nudity was used as a promotional strategy in the Polish cinema in the 1980s. In contrast to earlier decades, the Polish movie industry delivered dozens of films that contained female nudity and erotic scenes. Some actresses like Maria Probosz, became automatically associated with such movies. Paradoxically, the Polish cinema of the 1980s was only slightly concerned with the discourse of eroticism. As Maria Kornatowska writes,The shortage of erotic sensibility was compensated by ‘bald nakedness.’’ The reasons for the increased presence of nudity on movie screens stemmed from the transformation of social lifestyle and audiences’ demand, the search for easy profit and the need to de-politicize society. Of significant importance were the influences of the growing video market and western cinema. Projections of nudity were meant to divert attention from the bleak reality of Poland enmeshed in crisis provide a sense of belonging to the Western world, and give mostly male viewers visual pleasure. It was also a marketing technique luring viewers to cinemas by bombarding them with daring posters and stills reproduced in the press and in front of movie theaters. My article will discuss and explain the ways of presenting female nudity in terms of these economic and political tasks.